PENGARUH MOTIVASI BELAJAR, DUKUNGAN ORANG TUA, DAN SARANA PRASARANA SEKOLAH TERHADAP PEMBELAJARAN PENDIDIKAN JASMANI SISWA SEKOLAH DASAR NEGERI 01 LINGGOASRI TAHUN 2026 - Bayu Prayoga, Angga; Raharjo, Agus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to analyze the influence of learning motivation, parental support, and school facilities and infrastructure on Physical Education, Sports, and Health (PJOK) learning among students of SD Negeri 01 Linggoasri in 2026. This research employed a quantitative approach using an ex post facto survey design. The population consisted of 96 students in grades IV, V, and VI, and all participants were selected using the total sampling technique. Data were collected through Likert-scale questionnaires and analyzed using multiple linear regression with IBM SPSS Statistics. Before hypothesis testing, the data satisfied the assumptions of normality, multicollinearity, and heteroscedasticity. The findings revealed that learning motivation, parental support, and school facilities simultaneously had a significant effect on PJOK learning (F = 3.878; p = 0.012). However, partially, learning motivation (p = 0.530) and parental support (p = 0.225) did not significantly affect PJOK learning, whereas school facilities and infrastructure had a positive and significant effect (t = 2.594; p = 0.011). The coefficient of determination (R² = 0.112) indicated that the independent variables explained 11.2% of the variance in PJOK learning, while 88.8% was influenced by other factors outside the model. These findings highlight the importance of improving school facilities to enhance effective PJOK learning outcomes in elementary schools